(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2020)
This study aims to examines the financial literacy among university students in Syria using survey of 267 students from University of Kalamoon (UOK) and understand the influence of various factors influencing the financial literacy such as demographic, educational and personal financial characteristics. Mean, ANOVA and logistic regression were used in carrying out analysis using The Statistical Analysis Program (SPSS 25). Results show that most of the students have basic level of financial knowledge but they lack in understanding the advanced financial subjects. Students financial literacy is highly influenced by personal financial characteristics (89%) especially by the financial influence of their parents at home. The study further identified that financial literacy was (75%) affected by educational characteristics such as educational level, academic major, and (54%) by demographic characteristics such as age, gender, income. Students have to live a longer life ahead, thus, the decisions taken by them are going to affect them for a longer period of time, making it imperative for them to develop an understanding of the world of finance so as to avoid wrong choice of financial products. Thus, financial literacy is of significant relevance.